2004
DOI: 10.1074/jbc.m312243200
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Domain of Escherichia coli Lon Protease Has a Unique Fold and a Ser-Lys Dyad in the Active Site

Abstract: ATP-dependent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
187
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(191 citation statements)
references
References 61 publications
1
187
1
2
Order By: Relevance
“…Of the soluble ATP-dependent proteases within the AAA + superfamily, Lon more closely resembles proteases within the proteasome family (26,27,29,42). As such, we began our search for a Lon inhibitor by screening a series of commercially available peptide-based proteasome inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Of the soluble ATP-dependent proteases within the AAA + superfamily, Lon more closely resembles proteases within the proteasome family (26,27,29,42). As such, we began our search for a Lon inhibitor by screening a series of commercially available peptide-based proteasome inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The CapR9 mutant was later proved to carry a single amino acid mutation (E614K) on its C-terminal domain, which has a higher isoelectric point than that of the wild type (55). Judging from the three-dimensional structure of the proteolytic domain of E. coli Lon, the point mutation (E614K) is located at ␤-sheet 1 that plays an important role in forming the subunit interface (56). The crystal structure data also showed that the subunit interface is characterized by mostly hydrophilic interactions (56), implying that the hydrophilic interactions among subunit interfaces stabilize the oligomerization.…”
Section: The N-terminal Domain Of Lon Proteases Is Essential Formentioning
confidence: 99%
“…Judging from the three-dimensional structure of the proteolytic domain of E. coli Lon, the point mutation (E614K) is located at ␤-sheet 1 that plays an important role in forming the subunit interface (56). The crystal structure data also showed that the subunit interface is characterized by mostly hydrophilic interactions (56), implying that the hydrophilic interactions among subunit interfaces stabilize the oligomerization. In our experiments, Bt-LonN316 mutant lacking the C-terminal domain forms an octamer as the major species and a dimer as the minor one by analytical gel filtration chromatography.…”
Section: The N-terminal Domain Of Lon Proteases Is Essential Formentioning
confidence: 99%
“…Purified sensor and substrate discrimination domain binds to known Lon substrates (10), suggesting that it plays a role in substrate recognition. Although E. coli Lon is thought to be a homo-tetramer or -octamer, recent structural analysis of the proteolytic domain of Lon revealed that it assembles into hexameric rings (11).…”
mentioning
confidence: 99%